INDIRECT EFFECTS OF CHLORPYRIFOS ON THE HYPOTHALAMIC-PITUITARY NEUROSECRETORY SYSTEM OF RAT OFFSPRING - Dzhumaniyazov Shavkat Atanazarovich (Journal of Science in Medicine and Life, 2024)
The results of the effect of the organophosphorus pesticide chlorpyrifos on the hypothalamic-pituitary neurosecretory system of rat offspring, in case of poisoning during pregnancy and lactation, are presented. In all series of experiments, dose-dependent changes in the HPA axis of the offspring were observed, characterized by inhibition or some activation of the development and functioning of this system.